2001
DOI: 10.1209/epl/i2001-00290-6
|View full text |Cite
|
Sign up to set email alerts
|

Ion phase space vortices in 3 spatial dimensions

Abstract: The formation and propagation of isolated ion phase space vortices are observed in a 3-dimensional numerical simulation. The code allows for an externally applied constant magnetic field. The electrons are assumed to be isothermal and Boltzmann distributed at all times, implying that Poisson's equation becomes nonlinear for the present problem. Ion phase space vortices are formed by the nonlinear saturation of the ion-ion two-stream instability, excited by injecting an ion beam or short ion-bursts at the bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 22 publications
(32 reference statements)
4
19
0
Order By: Relevance
“…The conspicuous features of the potential structures seem to be associated with phase space vortices, where all the relevant dynamics seem to take place in {x, v x }-plane, as expected for potential structures elongated in the y-direction, as here. Such ion phase space vortices are well-known, and have been observed experimentally by Pécseli et al (1981Pécseli et al ( , 1984, as well as in a number of numerical simulations (Sakanaka, 1972;Børve et al, 2001;Daldorff et al, 2001;. In particular, the coalescence seen in Fig.…”
Section: Numerical Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The conspicuous features of the potential structures seem to be associated with phase space vortices, where all the relevant dynamics seem to take place in {x, v x }-plane, as expected for potential structures elongated in the y-direction, as here. Such ion phase space vortices are well-known, and have been observed experimentally by Pécseli et al (1981Pécseli et al ( , 1984, as well as in a number of numerical simulations (Sakanaka, 1972;Børve et al, 2001;Daldorff et al, 2001;. In particular, the coalescence seen in Fig.…”
Section: Numerical Resultssupporting
confidence: 61%
“…The present code allows for an externally applied magnetic field , but for the present results we consider an unmagnetized plasma. Phase space structures can be formed in magnetized plasma as well Daldorff et al, 2001;Jovanović and Shukla, 2003).…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…Numerical and theoretical studies of the interaction between the electron and ion holes have since then been performed by several authors. Newman et al [8] studied numerically the dynamics and instability of 2D phase-space tubes, whereas Daldorff et al [9] investigated the formation and dynamics of ion holes in three dimensions. Krasovsky et al [10] showed theoretically and by computer simulations that the electron holes perform inelastic collisions.…”
Section: Introductionmentioning
confidence: 99%
“…Newman et al (2001) in their numerical experiments studied the dynamics and instability of twodimensional phase-space tubes, and Daldorff et al (2001) investigated the formation and dynamics of ion holes in thee dimensions. Krasovsky et al (1999) showed theoretically and by computer simulations that that electron holes perform inelastic collisions, and Vetoulis (2001) studied the radiation generation due to bounce resonances in electron holes.…”
Section: Introductionmentioning
confidence: 99%